Exploring Intercultural Experiences among students in Malaysian’s Campus - Ismail, Puteri Nur Ily Amalina; Dalib, Syarizan (2018)
The process of globalization creates the opportunities to the people to build multicultural population in many parts of the world. The existence of multicultural population means that individuals need to accept and live with those who come from diverse cultural backgrounds. This advantages create a competency between individuals in order to face the globalization era. This study aims to explore student perspectives intercultural competence based on their experiences.